Konstruksi Identitas dan Nilai-Nilai Islam dalam Jargon “Go Berkah No Riba”: Analisis Wacana pada Komunikasi Pemasaran Digital - Suci Nabila; Viro Dharma Saputra (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the phenomenon of the religious jargon “Go Berkah No Riba” (Go Blessed, No Interest) as a digital marketing communication strategy employed by entrepreneurs on social media, particularly Facebook. Using a descriptive qualitative approach and visual discourse analysis, this research seeks to understand how the jargon is interpreted, constructed, and widely disseminated in the context of product marketing and business opportunities. The findings indicate that “Go Berkah No Riba” functions not only as a marker of religious identity but also as a rhetorical device that combines spiritual values with aspirations for material success. Visual analysis of promotional materials, such as flyers and Facebook posts, reveals the use of hyperbolic language, symbolic imagery—such as the Kaaba and piles of money—and religious narratives designed to build credibility and persuade potential consumers. The integration of religious elements with economic appeal creates a sharia-compliant business image that simultaneously promises profitability. However, the study also uncovers ambiguity in the use of this jargon. On the one hand, it can strengthen the image of a business operating ethically according to Islamic principles. On the other hand, it risks being exploited merely as a marketing gimmick without a strong foundation in ethical business practices. This creates the potential for a gap between the religious message communicated and the actual business conduct. The findings underscore the importance of critical literacy in understanding religious communication strategies within the digital business sphere. Consistency between religious messaging and real-world business practices is crucial for maintaining consumer trust and avoiding the excessive commodification of religious values. Therefore, this study contributes to a deeper understanding of the dynamics of religion-based marketing communication in the era of digital transformation.